READING STRATEGIES AS MODERATORS AND MEDIATORS IN EFL READING COMPREHENSION: A SYSTEMATIC REVIEW OF PERSONALITY-BASED DIFFERENCES - Muzdalifah Misbah; Kalsum Kalsum (Sekolah Tinggi Keguruan dan Ilmu Pendidikan Darud Da'wah Wal Irsyad Pinrang, 2026)
This study aims to synthesize empirical evidence on the relationship between personality traits, reading strategies, and English as a Foreign Language (EFL) reading comprehension, with a specific focus on the roles of reading strategies as mediators and moderators. Although previous studies have examined personality traits and reading strategies separately, findings remain fragmented and inconclusive regarding when and how reading strategies influence the relationship between personality and reading comprehension. To address this gap, a systematic literature review was conducted following PRISMA guidelines. Thirty empirical studies published between 2016 and 2025 were identified through searches of major academic databases, including Scopus, ERIC, Google Scholar, and ScienceDirect, and were screened and appraised for methodological quality before being analyzed thematically. The findings reveal that reading strategies predominantly function as moderators, indicating that their effectiveness depends on specific instructional and contextual conditions, particularly in relation to introversion–extroversion differences. In contrast, evidence supporting the mediating role of reading strategies remains limited and is mainly found in studies employing advanced analytical approaches, such as structural equation modeling. This review suggests that reading strategies operate both as conditional factors determining when personality traits influence reading comprehension and as potential cognitive–metacognitive mechanisms explaining how such influence occurs. The study highlights the need for future research to adopt process-oriented designs that simultaneously examine mediation and moderation to advance theory and practice in EFL reading instruction.